Transformasi Cerita Rakyat Lokal menjadi Cerpen Modern melalui Media Canva sebagai Upaya Meningkatkan Kemampuan Menulis Siswa Kelas X SMK - Desti Kusmayanti (Paedagogie, 2026)
This study aims to determine the effect of transforming local folktales into modern short stories using Canva on the writing skills of students at SMK Bintar Jalancagak. The method used in this research was an experimental approach with a quasi-experimental design involving an experimental class and a control class. Data collection techniques were carried out through tests in the form of pretests and posttests. The data obtained were analyzed using SPSS through normality tests, homogeneity tests, and hypothesis testing using the Mann-Whitney Test. The results showed that there was an improvement in learning outcomes in both groups; however, the increase in the experimental class was more significant than in the control class. The average pretest score of the experimental class increased from 57.86 to 81.57 in the posttest, while the control class increased from 61.14 to 72.71. The normality test indicated that the data were not normally distributed, and the homogeneity test showed that the data variance was heterogeneous; therefore, a non-parametric test, namely the Mann-Whitney Test, was used. The hypothesis test results showed that the Asymp. Sig. (2-tailed) value was 0.002 < 0.05, indicating a significant difference between the two groups. Thus, it can be concluded that the transformation of local folklore into modern short stories through Canva media has a positive and significant effect on improving the writing skills of tenth-grade students at SMK Bintar Jalancagak. Keywords: transformation of local folklore, modern short stories, Canva media, writing skills.